Fruit and Vegetable consumption and overweight among school-age children within the “COSI” Portuguese Study - Rito, Ana Isabel (2012)
Introduction: Overweight among children has increased dramatically in the last few years and various environmental, genetic and social factors have been associated with weight gain. Promoting fruit and vegetable consumption among children might be useful strategy for weight management in children. However evidence for the association between fruit and vegetable consumption and being overweight in childhood are inconsistent. The present study aims to describe fresh fruit, “100% Juice”, vegetables and soup (FJVS) consumption among children and examine whether low consumption of FJVS is associated with overweight in a sample of Portuguese schoolchildren. Methods: Children´s overweight and obesity prevalence estimate was obtained from the first data collection (2008) of the new National Nutritional Surveillance System- “COSI Portugal” among the seven geographic Regions (North, Centre, Lisbon and Tagus Valley, Alentejo, Algarve, Azores and Madeira). Children’s dietary intake was measured using a semi-quantitative Food Frequency Questionnaire completed by the parents. Overall, 3225 questionnaires were returned. Height and weight were measured according to international standards, and BMI was calculated. To determine the magnitude of the association between FJVS consumption and overweight, crude Odds Ratio estimates, including CI, were computed using unconditional logistic regression. Results: 3812 children were included in the analyses (50,3% boys with a mean age (±SD) of 7,03 years ±0,72). Using Portuguese Health General Directorate terminology which uses CDC (2000) criteria for defining nutritional status 32,1% children were overweight (IMC ≥P85) , 14,5% were obese (IMC ≥P95) and 2,2% were underweight(IMC≤P5) . According to children’s FJVS consumption only 2%, 3,5% and 1,8% ate fresh fruit, vegetables and soup every day, respectively. Otherwise, 21,6% children consume 100% fruit juice every day. There was no difference between FJVS consumption among boys and girls, except for the soup consumption that was higher in girls (p=0,01). There were also no differences between FJVS consumption among age groups. Normal weight children ate FJVS more frequently than overweight and this differences were statistically significant for fresh fruit consumption (p=0,012). With regard to FJVS consumption (≥4 times/week and <4 times/week), no differences between overweight and non-overweight children were found for fresh fruit (<4 times/week: OR=1,03, 95% CI 0,86-1,24), 100% juice (≥4 times/week: OR=1,11, 95% CI 0,93-1,32) and soup consumption (<4 times/week: OR=1,12, 95% CI 0,91-1,38). However the consumption of vegetables less than 4 times a week shown to be a risk factor for overweight children (OR=1,20, 95% CI 1,02-1,40). Conclusions: The low intake of vegetables was associated with increased risk of overweight in Portuguese schoolchildren.